Quantum probe of Horava-Lifshitz gravity - Gurtug, O.; Mangut, M. (Amer Inst Physics, 2018)
Particle probe analysis of the Kehagias-Sfetsos black hole spacetime of Horava-Lifshitz gravity is extended to wave probe analysis within the framework of quantum mechanics. The time-like naked singularity that develops when omega M2 < 1/2 is probed with quantum fields obeying Klein-Gordon and Chandrasekhar-Dirac equations. The quantum field probe of the naked singularity has revealed that both the spatial part of the wave and the Hamiltonian operators of Klein-Gordon and Chandrasekhar-Dirac equations are essentially self-adjoint, and thus, the naked singularity in the Kehagias-Sfetsos spacetime becomes quantum mechanically non-singular. Published by AIP Publishing.
Keywords: Kehagias-Sfetsos Solution; Singularities; Spacetimes; Constraints